Azulejo, cultura, memória e sociedade: para um estudo dos significados sociais do património azulejar - Menezes, M. (2015)
This reflection is part of a wider interest in the study of the social processes of development of cultural heritage. Based on the knowledge of how these values are formed and represented, this more ambitious purpose is oriented towards the identification of how social and symbolic meanings related to cultural heritage can, in a dynamic, interactive and negotiated way, collaborate with protection and conservation practices. As a general framework, it is assumed that the process of heritage invention is a social practice, simultaneously mentioning that so are also are the preservation and conservation, which require social involvement and other types of commitment. In fact the tile heritage is no exception to this starting frame. Therefore, this reflection whose goals are more modest, illustrates some of the preambles leading to the interest in starting a research on the social meanings associated with the azulejo (ceramic tile) integrated in architecture. The focus of the reflection is the Portuguese context, where it is supposedly consistent to refer that the azulejo is a secular element of material culture: present with special relevance in the country's cultural landscape and presenting itself as an identity marker; with a permanent place in a national museum, the tile material comprises the contents that define the heritage category, protagonist in the internationalization of the country. The significant exaltation of the expression of tile matter is echoed in several different contexts, discourses and representations. Values of use, function, artistic, decorative and aesthetic, historical, technical and scientific, support the secular tile culture, potentially setting a cultural uniqueness that is plural in diversity through which styles, themes, textures, materials, techniques, colours and patterns are revealed to the eyes of careful observers. However, the secular taste for azulejo also seems to reveal an ambiguous relationship of people and communities with the tile as a material, recognized in the relationship of simultaneous affection and disaffection, reflecting the enhancement in the use of tiles and its trivialization, due to the habit of using and seeing them. What do the appreciable demonstration of enjoyment for the tile, and the manifestations of carelessness, disinterest, vandalization and substitution explain about the relationship between society and heritage? This first perplexity of the relationship of people and communities with the azulejo is the initiatic preamble of an anthropologist to learn about the social universe that covers the culture of the ceramic tile. Therefore, this reflection raises questions about the potential interest of broadening the scope of comprehending azulejo heritage also to its social meaning.